Inhaled corticosteroid therapy is safe in tuberculin-positive asthmatic children - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2000)
Background. Although treatment with oral corticosteroids can cause reactivation of latent Mycobacterium tuberculosis (TB) infection in purified protein derivative (PPD)-positive individuals with no evidence of clinical disease, little is known about the effects of inhaled corticosteroids in this respect. Objective. This study was undertaken to assess whether inhaled corticosteroid (CS) therapy reactivates latent TB infection in PPD-positive asthmatic children. Method. We studied 32 PPD skin test-positive (greater than or equal to 10 mm) children [age (mean +/- SD), 7.9 +/- 4.1 years] with no family history and no evidence of TB infection on chest radiograms who were receiving inhaled budesonide for the treatment of asthma. They were further evaluated with thorax computed tomography (CT) and erythrocyte sedimentation rate and closely observed for an additional 9 months. Results. At enrollment the mean diameter of PPD reaction was 12.8 +/- 2.7 mm, The mean duration of inhaled CS treatment and the mean cumulative CS dose were 9.8 +/- 7.6 months and 275 +/- 199 mg, respectively. Thorax CT studies revealed mediastinal lymph nodes in 7 of the 32 patients. There was no significant difference between children with and without mediastinal lymph nodes according to age, gender, size of PPD skin testing, erythrocyte sedimentation rate and duration and cumulative CS dose of inhaled budesonide therapy before study. A second thorax CT was obtained 9 months later in those 7 patients with lymphadenopathy (additional mean cumulative CS dose, 222.57 mg), There was no change in the size of their lymph nodes. Conclusion. Long term inhaled budesonide therapy appears to be safe in PPD-positive asthmatic children.
Keywords: asthma; inhaled budesonide; purified protein derivative; tuberculosis